ӘЖИНИЯЗ ҚОСЫБАЙ УЛЫ ЖАСЛАР ТӘРБИЯСЫ МӘСЕЛЕЛЕРИ ҲАҚҚЫНДА - Әлеўов, Ө.; Таспанова, Ж.К. (FAN va JAMIYAT, 2020)
The article tells about the religious direction of Sufism. Mainly the teaching of Sufism has a great influence on the historical and cultural, mainly spiritual development of all mankind, on the prosperity of civilization. The derection tasawwuf emphasizes that it was God who created the world.